2022
DOI: 10.1186/s40900-022-00373-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-designing a cancer care intervention: reflections of participants and a doctoral researcher on roles and contributions

Abstract: Background Patient and Public Involvement is most usually framed in the context of designing, conducting and/or disseminating research. Participatory methods such as Experience-Based Co-Design (EBCD) further allow service users to directly engage in developing, testing and implementing interventions and services alongside healthcare staff. This paper aims to explore how participants in an EBCD project came—over time—to perceive their role and involvement in co-designing a cancer care interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…This requires defining the parameters and having a shared understanding of the co‐production process at the start of the project. In agreement with existing evidence, having a shared understanding of the co‐production process is one of the determinants of success in co‐produced projects 9 . This is reflected in our proposed virtuous cycle.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This requires defining the parameters and having a shared understanding of the co‐production process at the start of the project. In agreement with existing evidence, having a shared understanding of the co‐production process is one of the determinants of success in co‐produced projects 9 . This is reflected in our proposed virtuous cycle.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Oliver et al suggested a ‘cautious approach’ to co‐production to maximise its benefits over the costs 3 . A common principle that is inherent in co‐produced research is that of sharing 1,9 . The INVOLVE guidance published in 2018 highlight the sharing of power and responsibilities 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations